(untitled) (UNWE Yearbook, 2020)
The article explains the specificities of the Bulgarian social policy model, relating its implementation to the prevailing paradigm of public governance and its dissemination. For the purpose, the author asserts the important role of ideas and knowledge for the adoption of concrete policy principles, goals and instruments. Finally, based on the social results of the Bulgarian social policy model, the author discusses its prospects for future development.